Sodium-glucose cotransporter-2 inhibitors: current knowledge on the use of canagliflozin, dapagliflozin and empagliflozin in the treatment of type 2 diabetes mellitus - Martha Lilac Ketisha Antoine, Malyn; Xu, Yancheng (International Journal of Medicine, 2020)
Sodium-glucose cotransporter-2 inhibitors are considered the newest class of medication developed for the treatment of type 2 diabetes mellitus. This class of drug reduces blood glucose levels by decreasing glucose absorption at the level of the kidneys. Through their mechanism of action, drugs within this class exhibit the ability to reduce blood pressure, fasting blood glucose and body weight. The common side effects observed with the use of sodium-glucose cotransporter-2 inhibitors include: genital mycotic infections, intravascular volume depletion and dehydration. To date, much is already known about Sodium-glucose cotransporter-2 inhibitors and their use in treating type 2 diabetes mellitus; however, continuous studies are currently being undertaken to further investigate the cardiovascular benefits and side effect profile of this class of drug. This review discusses sodium glucose cotransporter-2 inhibitors specifically focusing on what is currently known about the use of canagliflozin, dapagliflozin and empagliflozin in the treatment of type 2 diabetes mellitus.Â